IMPLEMENTASI KEBIJAKAN PENGELOLAAN AIR LIMBAH DOMESTIK DI KECAMATAN TUALANG (Studi Kasus Perda Kab.Siak No.1 Tahun 2017) - Sindriani Dakhi; Sujianto Sujianto (Cross-border, 2023)
Domestic wastewater is one of the most complex issues causing various problems that should be prioritized by the community and the government. This does not mean that this problem is not handled at all, but its management can still be described as poorly organized. Therefore, this research was carried out by looking at the extent of domestic wastewater management in Tualang District, Siak Regency with the theory used is Van Meter Van Horn. Qualitative research method with a case study approach. From this research, the results obtained are that domestic wastewater management in Tualang Subdistrict is very inefficient in terms of time cooperation with the community. This research also shows that population density causes limited land for sanitation development, which is only equipped with a Fecal Sludge Management Unit (IPLT), from the community side it is also still indifferent, other findings also show that population density makes land for sanitation development limited and people lack understanding of the impact of domestic wastewater. Recommendations from this research for implementing agents with communities that still lack participation, it would be better if the community is first empowered technically and knowledge of the dangers of domestic waste, also empowered how the habit of protecting the environment so that from this habit, the community can protect the environment, as the saying can ala usual so that thus, domestic wastewater treatment can reduce the level of environmental contamination and help protect public health.